Atypical child development in context - Empson, Janet M. (Janet Margaret), 1947- (2015)
"The book considers the important issue of what is 'normal' and what is 'atypical' in child development. It examines the main processes involved in developing atypically, as well as the circumstances and conditions associated with it. The second edition is fully updated and features new research, case studies, real-life examples and figures"--
Includes bibliographical references (pages 205-240) and index.
Keywords: Child development; Child development deviations; Children with social disabilities; Developmentally disabled children; Child psychopathology; MEDICAL / Allied Health Services / General; PSYCHOLOGY / General; PSYCHOLOGY / Developmental / Child; PSYCHOLOGY / Developmental / General